The office of historical corrections eaudiobook A novella and stories. - Evans, Danielle (Penguin Audio, 2020)
WINNER OF THE 2021 JOYCE CAROL OATES PRIZE NAMED A BEST BOOK OF 2020 BY O MAGAZINE, THE NEW YORKER, THE WASHINGTON POST , REAL SIMPLE, THE GUARDIAN, AND MORE  FINALIST FOR: THE STORY PRIZE, THE L.A. TIMES BOOK PRIZE, THE ASPEN WORDS LITERARY PRIZE, THE CHAUTAUQUA PRIZE “Sublime short stories of race, grief, and belonging . . . an extraordinary new collection . . .” — The New Yorker   “Evans’s new stories present rich plots reflecting on race relations, grief, and love . . .” — The New York Times Book Review , Editor’s Choice “Danielle Evans demonstrates, once again, that she is the finest short story writer working today.” —Roxane Gay, The New York Times –bestselling author of Difficult Women and Bad Feminist The award-winning author of Before You Suffocate Your Own Fool Self brings her signature voice and insight to the subjects of race, grief, apology, and American history. Danielle Evans is widely acclaimed for her blisteringly smart voice and X-ray insights into complex human relationships. With The Office of Historical Corrections , Evans zooms in on particular moments and relationships in her characters’ lives in a way that allows them to speak to larger issues of race, culture, and history. She introduces us to Black and multiracial characters who are experiencing the universal confusions of lust and love, and getting walloped by grief—all while exploring how history haunts us, personally and collectively. Ultimately, she provokes us to think about the truths of American history—about who gets to tell them, and the cost of setting the record straight. In “Boys Go to Jupiter,” a white college student tries to reinvent herself after a photo of her in a Confederate-flag bikini goes viral. In “Richard of York Gave Battle in Vain,” a photojournalist is forced to confront her own losses while attending an old friend’s unexpectedly dramatic wedding. And in the eye-opening title novella, a black scholar from Washington, DC, is drawn into a complex historical mystery that spans generations and puts her job, her love life, and her oldest friendship at risk.